Fracture resistance of weakened premolars restored with sonically-activated composite, bulk-filled and incrementally-filled composites(A comparative in vitro study) - Fahad, Fatima; Majeed, Manhal A (Journal of Baghdad College of Dentistry, 2014)
Background: This study was conducted to assess the effect of sonic activation and bulk placement of resin composite in comparison to horizontal incremental placement on the fracture resistance of weakened premolar teeth. Materials and method: Sixty sound human single-rooted maxillary premolars extracted for orthodontic purposes were used in this study. Teeth were divided into six groups of ten teeth each: Group 1 (sound unprepared teeth as a control group), Group 2 (teeth prepared with MOD cavity and left unrestored), Group 3 (restored with SonicFillâ„¢ composite), Group 4 (restored with Quixfilâ„¢ composite), Group 5 (restored with Tertic EvoCeramÂ® Bulk Fill composite) and Group 6 (restored with Universal Tetric EvoCeramÂ® composite using horizontal incremental layering technique). Standardized class II MOD cavity was prepared in all teeth except (group 1).After finishing the restorative procedure of each group according to the manufacturer’s instructions, all teeth were stored in deionized distilled water in an incubator at 37Â°C for seven days.All specimens were subjected to compressive axial loading until fracturein a universal testingmachine.Specimens were examined by a stereomicroscope at a magnification of (20X) to evaluate the mode of fracture . Results: The results of this study revealed that the control group exhibited the highest fracture resistance compared to all prepared teeth groups (restored or unrestored) and the differences were statistically highly significant (P